Arithmetic of influence of debt crisis on economies of Visegrad Group and challenges ahead - Ptak, Piotr (Economics of the 21st Century, 2014)
The global financial and economic crisis has fully revealed the risks of over-indebted countries, whose cause was, inter alia, the maintenance of structural deficits for many years. Economies of the Visegrad Group (V4 Group) conducted even less disciplined fiscal policy than the EU. Nevertheless, the V4 Group has weathered the crisis better than the EU, even though its initial fiscal position was worse. However, in the long term, the fiscal consolidation process will be hindered due to unfavorable demographic trends and the burden on public finances imposed by scarce social security systems. In this respect, the V4 Group is going to experience even greater challenges than the EU. The purpose of this article is to show the arithmetic course and consequences of the sovereign debt crisis on economies of V4 Group as well as the challenges related among others to ageing process its population is going to face in medium and long term
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 64-79
Keywords: V4 Group; sovereign debt crisis; general government debt; fiscal consolidation; ageing of population; Grupa Wyszehradzka; kryzys zadłużenia suwerennego; dług publiczny; konsolidacja fiskalna; starzenie się społeczeństwa